An analysis of the correlation between diabetic retinopathy and preretinal oxygen tension using three-dimensional spoiled gradient-recalled echo sequence imaging - Min-Jie Zhou; Ju-Wei Shao; Jian Pu; Shu-Tian Xiang; Yi Liang; Qian He; Wei Su; Cheng Liu (BMC Medical Imaging, 2022)
Abstract Background The aims of this study were to evaluate the levels of preretinal oxygen tension in patients with diabetes who did not have hypertension by using three-dimensional spoiled gradient-recalled (3D-SPGR) echo sequence imaging and to explore the correlation between diabetic retinopathy (DR) and changes in preretinal oxygen tension. Method This study involved 15 patients with type 2 diabetes without hypertension, who were divided into a diabetic retinopathy (DR) group (n = 10 eyes) and a diabetic non-retinopathy (NDR) group (n = 20 eyes), according to the results of a fundus photography test. Another healthy control group (n = 14 eyes) also participated in the study. The preretinal vitreous optic disc area, nasal side, and temporal side signal intensity of the eyes was assessed before and after oxygen inhalation with the use of 3D-SPGR echo magnetic resonance imaging (MRI). The signal acquisition time was 10, 20, 30, 40, and 50 min after oxygen inhalation. Results The results showed that, in the DR and NDR groups, the preretinal vitreous oxygen tension increased rapidly at 10 min after oxygen inhalation and peaked at 30–40 min, and the increased slope of the DR group was higher than that of the NDR group. The oxygen tension of the preretinal vitreous gradually increased after oxygen inhalation, and the difference between the DR and NDR groups and the control group was statistically significant (P < 0.05). The preretinal vitreous oxygen tension was higher in the optic disc, temporal side, and nasal side in the NDR group than in the control group, and the difference was statistically significant (P < 0.05). The maximum slope ratios of the optic disc and the temporal side of the DR group were greater than those of the control group, and the difference was statistically significant (P < 0.05). Conclusion Three-dimensional-SPGR echo MRI sequencing technology is useful for detecting preretinal oxygen tension levels in patients with diabetes. It can be used as one of the functional and imaging observation indicators for the early diagnosis of DR.